1991
DOI: 10.1152/ajpregu.1991.260.2.r321
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intracerebroventricular injection of neuropeptide Y on energy metabolism

Abstract: Our objective was to find out if central injection of neuropeptide Y (NPY) would alter brown fat thermogenesis and white fat lipoprotein lipase activity. The following three groups of Sprague-Dawley rats received five injections over 24 h into the right lateral ventricle: 1) NPY (5 micrograms/injection) and ad libitum food; 2) NPY (5 micrograms/injection) and food restricted to control intake; 3) saline injection and ad libitum food. The NPY ad libitum-fed group consumed more food than the saline controls or N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
188
2
2

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(198 citation statements)
references
References 33 publications
6
188
2
2
Order By: Relevance
“…It has been suggested that centrally administered NPY increases the expression of LPL mRNA and enhances LPL activity in white adipose tissue thus favoring lipid storage (Billington et al, 1991(Billington et al, , 1994. In the present study, the heparin-releasable LPL activity did not differ among the genotype groups.…”
Section: Leu7pro In Npy Gene and Lipid Response Us Schwab Et Alcontrasting
confidence: 50%
See 2 more Smart Citations
“…It has been suggested that centrally administered NPY increases the expression of LPL mRNA and enhances LPL activity in white adipose tissue thus favoring lipid storage (Billington et al, 1991(Billington et al, , 1994. In the present study, the heparin-releasable LPL activity did not differ among the genotype groups.…”
Section: Leu7pro In Npy Gene and Lipid Response Us Schwab Et Alcontrasting
confidence: 50%
“…However, disturbed liver uptake or catabolism of LDL could also play a role. NPY has been suggested to regulate LPL activity in adipose tissue of experimental animals (Billington et al, 1991(Billington et al, , 1994. This Table 2 Energy intake, proportion of energy nutrients, and the intake of dietary cholesterol and fiber during the run-in period and the reduced fat diet period, mean AE s.e.m.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several peptides, such as NPY and AgRP, which stimulate food intake also alter energy expenditure [22][23][24]. We therefore examined the acute effects of H3 on both plasma TSH and other parameters of energy expenditure (VO 2 , RER and ambulatory activity).…”
Section: Discussionmentioning
confidence: 99%
“…Primary among the functions associated with NPY are its acute effects on feeding behavior and energy expenditure. Injection of NPY into mice results in prolonged increases in food and water intake along with the suppression of metabolic rate (Billington et al, 1991;Schwartz et al, 2000). NPY knockout mice surprisingly experience no alterations in feeding behavior, implying a redundancy and/or multistep process in feeding signaling systems (Erickson et al, 1996a).…”
Section: Introductionmentioning
confidence: 99%